Neonatal antiphospholipid syndrome - Magalhães, Claudia Saad [UNESP]; de Souza, Ligia Maria Suppo Rugolo [UNESP]; Trindade, Cleide Enoir Petean [UNESP] (American Academy of Pediatrics (AAP), 2014)
Antiphospholipid antibody syndrome (APS) during pregnancy may result in pregnancy morbidity and passive transfer of antibodies to the fetus, resulting in an increased risk of prematurity, intrauterine growth restriction, thrombocytopenia, and developmental delay. Antiphospholipid antibodies may have an impact on neurodevelopment during fetal life. Although rare, persistence of these antibodies in the neonate may lead to thromboembolism, particularly if there is a concurrent infection and/or inherited thrombophilic disorders. Affected pregnant women need to be identified early during gestation so that they can have closemonitoring of the placental circulation, fetal growth and development, and testing of serum antiphospholipid antibody levels. Neonates born to mothers with antiphospholipid antibody syndrome should have close neurodevelopment follow-up. © 2014 by the American Academy of Pediatrics. All rights reserved.